The Impact of Quality Service and Price for the Satisfaction Customer on APRIL.COM Pematang Siantar - Wadi Sihombing; Benjamin Albert Simamora; Debbi Petra Meyana Sitorus (MultiTech Publisher, 2023)
The problem in this research is the lack of quality of customrt satisfaction. This research aims to determine the increase in customer satisfaction results by implementing service quality and price. This type of research is quantitative research carried out at APRIL.COM Pematangsiantar. The research subjects are incoming customers. Totaling 60 people. Data collection techniques in research are interviews, observation, documentation studies, and questionnaires to see customer satisfaction during the business process. Data analysis techniques are carried out in several stages, namely data quality testing, classical assumption testing, and hypothesis testing. Based on the coefficient of determination (R2), the adjusted R square value (is 0.590), which means that the influence of the independent variable (X) on variable Y is 59%. This can indicate that the variables Service quality (X1) and price (X2) explain the influence on the variable customer satisfaction customers at APRIL.COM Pematangsiantar is 59% while the remaining 41% is the influence of other independent variables that where not examined in this research. Thes factors include the location of APRIL.COM which is quite far from the campus area and main roads. Which will affect customers who come because there is competition within the same store and distance. It can be concluded that imp;ementing service quality and price can increase customer satisfaction at APRIL.COM Pematangsiantar in the coming year